Pengaruh Model Pembelajaran Kooperatif Tipe TPS Berbantuan Peta Konsep terhadap Penguasaan Kompetensi Pengetahuan IPA - Anggara, I Made Citra (Universitas Pendidikan Ganesha, 2018)
This research purpose to know the significant difference of the science learning outcomes between student is learned by model problem solving using environmental with student who is learned by conventional learning model fourth grade students of elementary school at Gugus Letkol Wisnu, North Denapasar sub-district. This research in an quasi experiment using Non-equivalent control group design. The population in this research are all the fourth grade students of elementary school at Gugus Letkol Wisnu, North Denpasar that formed by consisting of 340 students.. The accumulation data of science learning outcomes by test method and instrument that use is either be multiple choice objective test. Obtained data is analyzed by using t-test. Based of analyze result obtainable thitung= 6,229 > ttabei=2,000, on dk 83 level of significance 5%. So, that HO ignored and Ha acceptable means there is a significant difference competence science the learning with learning comparative type TPS aided concept maps with students learn with learning conventional. Mean of science learning outcomes result in experiment group is 84,10 and in control group is 73,20. Therefore, can be concluded that model problem solving using environmental take effect to the science learning outcomes of fourth grade students Gugus Letkol Wisnu, North Denpasar sub-district.